CHALLENGES AND OPPORTUNITIES FOR WIND POWER FOR FUTURE ENERGY SUPPLIES IN PAKISTAN - Farooque, M.; Javed, M. T.; Waheed, K.; Khan, N. A. (The Nucleus, 2020)
Due to rapid modernization the energy resources are depleting rapidly throughout the world while the energy demand is rising steadily. The crude oil price has soared upto $140.0 per barrel that has triggered the use of renewable energy recourses. Pakistan particular is the most energy deficient country where a shortfall of as high as 4500 MW is recorded in the recent year. The Renewable Energy Technologies (RET’s) are important and had gained the prime importance these days with specific focus on solar and wind power. This paper highlights the challenges and opportunities for wind power in Pakistan. The wind potential in different areas has been explored, including a vital area of about 9700 km2 in Sindh. Wind power is a new energy resource in Pakistan’s history, uptil now main resources are Fossil Fuel contributing 65%, hydel 33% and nuclear only 2% respectively. Wind is an environment friendly resource and its appreciable contribution will be achieved in future. Paper analyses the present energy scenario through wind power in Pakistan and leads to future progress in order to secure energy security in the country.